2021
DOI: 10.1371/journal.pone.0248365
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between myopericarditis and acute myocardial infarction on presentation in the emergency department using the admission C-reactive protein to troponin ratio

Abstract: Background The treatment of myopericarditis is different than that of acute myocardial infarction (AMI). However, since their clinical presentation is frequently similar it may be difficult to distinguish between these entities despite a disparate underlying pathogenesis. Myopericarditis is primarily an inflammatory disease associated with high C-reactive protein (CRP) and relatively low elevated troponin concentrations, while AMI is characterized by the opposite. We hypothesized that evaluation of the CRP/tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In one study, the CRP to troponin ratio of more than 250 was determined to have a specificity of more than 85% in differentiating myopericarditis from acute myocardial infarction. This further emphasizes the validity of myopericarditis as the final diagnosis considering the CRP/Troponin value for this patient was approximately 430 [8] .…”
Section: Discussionsupporting
confidence: 54%
“…In one study, the CRP to troponin ratio of more than 250 was determined to have a specificity of more than 85% in differentiating myopericarditis from acute myocardial infarction. This further emphasizes the validity of myopericarditis as the final diagnosis considering the CRP/Troponin value for this patient was approximately 430 [8] .…”
Section: Discussionsupporting
confidence: 54%
“…7 The electrocardiogram (ECG) may indicate ischemic alterations or even imitate an ST-segment elevation myocardial infarction in cases of myopericarditis, which can resemble AMI and present promptly with typical ischemic symptoms (STEMI). 8 Acute pericarditis was discovered to be a substantial cause of cardiovascular hospitalizations in 1.7% of patients with ST-segment elevation in those in whom myocardial infarction had been ruled out. 4,9 In general, males had a higher chance of having pericarditis than women do, and when age increased by a decade, the number of pericarditisrelated hospital admissions fell by an estimated 51%.. 9 In our case, the patient complaining pleuritic chest pain and diffuse ST elevation from the ECG which met 2 of 4 diagnostic criteria for acute pericarditis according to European Society of Cardiology (ESC).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to AMI patients, myopericarditis patients can have at admission acute chest pain, electrocardiographic changes and elevated cTns levels, making complicated the distinction between myopericarditis and AMI 62 . In a very recent study, Meisel et al suggested the use of CRP/troponin ratio as a tool to differentiate among AMI and myopericarditis patients 62 . Considering that the myopericarditis is an inflammatory disease, a CRP/troponin ratio > 250 “could indicate” the presence of myopericarditis, while a CRP/troponin ratio > 500 “could confirm the diagnosis” of a cardiac inflammatory condition in patients presenting with an acute cardiac syndrome when the clinical circumstances suggest low pre‐test probability of obstructive coronary artery disease 62 …”
Section: Cardiac Troponins As Biomarkers In Non‐ami Diseasesmentioning
confidence: 99%
“…107 The use of several techniques for protein analysis allowed to understand that cTnI and cTnT can be found in the blood either as cTns complex, as intact proteins, or degradation protein products. 62 By the use of western blot analysis, Madsen et al observed in a group of 26 male patients with acute STEMI, treated with thrombolytic drugs, that intact cTnI and a single degradation product (24 and 20 kDa, respectively) were detectable as early as 90 min after onset of symptoms with further degradation (up to 7 degradation products) after 165 min. 109 Cardinaels et al employed gel filtration chromatography (GFC) and western blot analysis to establish which cTnT forms circulate in the blood of AMI patients.…”
Section: Unsolved Issues Related To Ctns In Peripheral Circulationmentioning
confidence: 99%
See 1 more Smart Citation